The Urgency of Identity Verification and Safeguarding Personal Information During Online Transactions - Satila, Anton; Sudirman; Fadjriah Hamzah, Ismi; Umar, Wahyudi; Wetzal, Matthias (Law and Justice, 2024)
The complexity of law enforcement in online trading fraud cases poses significant challenges. Sellers can carry out fraudulent activities through product counterfeiting or making transactions outside of e-commerce platforms, while buyers can commit fraud by falsifying identities and making fake orders. Despite efforts to address this problem through legal remedies, the prevalence of fraud has not decreased. In the normative research study, fraudulent behavior is studied related to the provisions contained in the ITE Law and the Personal Data Protection Law. These findings underscore the importance of implementing authentication measures to verify the identity of sellers and buyers during online interactions. Authentication methods like this can significantly reduce fraud by allowing for quick identification of perpetrators and tracking of their fraudulent activities, ultimately deterring them from engaging in fraudulent behavior.     Kompleksitas penegakan hukum dalam kasus penipuan perdagangan online menimbulkan tantangan yang signifikan. Penjual dapat melakukan kegiatan penipuan melalui pemalsuan produk atau melakukan transaksi di luar platform e-commerce, sementara pembeli dapat melakukan penipuan dengan memalsukan identitas dan membuat pesanan palsu. Meskipun ada upaya untuk mengatasi masalah ini melalui upaya hukum, prevalensi penipuan tidak berkurang. Dalam studi penelitian normatif ini, perilaku penipuan dikaji dengan aturan yang terdapat dalam UU ITE dan UU Perlindungan Data Pribadi. Temuan ini menggarisbawahi pentingnya penerapan langkah-langkah otentikasi untuk memverifikasi identitas penjual dan pembeli selama interaksi online. Metode otentikasi seperti ini dapat secara signifikan mengurangi penipuan dengan memungkinkan identifikasi pelaku dan pelacakan aktivitas penipuan dengan cepat, yang pada akhirnya menghalangi pelaku untuk terlibat dalam perilaku curang.